Tahapan Perilaku Aktor Jaringan Komunikasi Pada Sosialisasi Isu Bullying - Ruvira Arindita; Yoedo Shambodo (Jurnal Komunikasi Global, 2019)
Bullying has been an alarming issue for kids and teenagers nowadays. One of community that shares serious concern over this issue is Sudah Dong. This study aims to find out how the behaviour stages of actors in creating the communication networks between the volunteers of Sudah Dong community by employing the qualitative approach with in-depth interviews and observation, and theory of actor network. The result of this research revealed that the main volunteers have done the six stages of behaviour to create communication network, including problemization, interessement, enrollment, mobilization, dan inscription. Few focal actors have become the strongest nodes of the communication network and contributed much to the existence of the community. Moreover, human collectivism such as supporting organizations and private sectors were also contributing factors for the network. The non-human factors namely events and media helped attract individuals to join as volunteers. This research also found that only a few main volunteers actively participated in the community, but it was relatively effective to run the community. The shared feelings towards bullying issues and the close friendships ties were the significant factors strengthening the communication network among the main volunteers.